The Effect of Stock Liquidity on the Firm’s Investment and Production - Amihud, Yakov; Levi, Shai (Review of Financial Studies, 2023)
Abstract We propose that stock market liquidity affects corporate investment and production. Illiquidity, which raises firms’ cost of capital, lowers investment in capital assets, R&D, and inventory. This effect holds after we control for endogeneity using exogenous liquidity events, the 2001 decimalization, and the 1997 Nasdaq reform and after employing instrumental variable estimation. Illiquidity affects investment regardless of firms’ financial constraints. Consequently, illiquidity induces firms to adopt less capital-intensive production processes. Illiquid firms have higher marginal productivity of capital, greater labor input increases for given increases in assets, and lower operating leverage, which means lower reliance on fixed costs.